Reform of the Policy on Public Debt Limits in Fund-Supported Programs. (Policy Papers; Policy Paper, 2014)
The reform of the Fund's policy on the use of conditionality on public external debt in Fund-supported programs (the 'debt limits policy') has been under discussion since March 2013. The discussion has taken place against a backdrop where lower income countries are seeking to boost growth through higher public investment levels, targeted in particular at large infrastructure gaps, while facing both a wider range of external financing opportunities and limits on the supply of traditional concessional financing. The reform of the Fund's policy on debt conditionality in 2009 was a first step to accommodate these new realities: experience with the 2009 reforms has pointed to the need for more fundamental reforms to provide countries with greater flexibility to finance productive investments while containing risks to medium-term debt sustainability. The reforms proposed here build on the Board review of the debt limits policy in March 2013, ensuing informal Board discussions in January and May 2014, discussions at an informal seminar in September 2014, and various stakeholder consultations. In developing this reform proposal, staff has sought to first specify a robust set of principles to guide the use of public debt conditionality in all Fund arrangements and then examine how these principles should apply in the specific circumstances of countries that normally rely on official external concessional financing.